Central banks Digital Currencies Issuance: Development Directions and Key Risks - V. V. Kuznetsova; O. I. larina (Финансы: теория и практика)
Currently, many central banks have begun to develop, study and introduce central bank digital currencies (CBDC). Due to the lack of sufficient experience, potential problems and risks’ research that can stimulate such financial innovations is relevant. The paper analyzes the projects for the creation of CBDC. The purpose of the paper is to identify unresolved aspects of the application of CBDC, and specific tasks include identifying the problems of the marketing of retail CBDC and the identification of the risks generated by them. The authors use general and special research methods, including comparative analysis and systematization. The article examines the prospects for digital ruble circulation in the Russian Federation. The use of CBDCs opens up enormous opportunities for the development of the digital economy, but their actual deployment is replete with risk. The article identifies the risks of the third form of national currency: technological (including environmental), economic, financial, social and legal. The authors consider that the widespread use of CBDC implies a transformation of the activities of national central banks, including a change in the role and functions of the national central bank, and provide several possible scenarios. The authors include among the unresolved problems that require solutions for the widespread practical use of digital securities: lack of understanding of the mechanism for transferring ownership during transfers from one user to another, clear prudential regulation, and effective management of big data analytics. Furthermore, the scope of regulation of the financial intermediation sector with regard to fintech innovations has not been defined; there is no system for exchanging data between different government agencies for a timely and more accurate assessment of potential risks; and the required number of specialists is not sufficient. The research can be important for both digital money consumers and authorities when the initiative to issue digital money in Russia is implemented.